Classroom Popularity Hierarchy Predicts Prosocial and Aggressive Popularity Norms Across the School Year. Issue 5 (2nd March 2019) - Laninga‐Wijnen, Lydia; Harakeh, Zeena; Garandeau, Claire F.; Dijkstra, Jan K.; Veenstra, René; Vollebergh, Wilma A. M.
Abstract : This study examined the coevolution of prosocial and aggressive popularity norms with popularity hierarchy (asymmetries in students' popularity). Cross‐lagged‐panel analyses were conducted on 2, 843 secondary school students ( N classrooms  = 120; M age  = 13.18; 51.3% girls). Popularity hierarchy predicted relative change in popularity norms over time, but not vice versa. Specifically, classrooms with few highly popular and many unpopular students increased in aggressive popularity norms at the beginning of the school year and decreased in prosocial popularity norms at the end of the year. Also, strong within‐classroom asymmetries in popularity predicted relatively higher aggressive popularity norms. These findings may indicate that hierarchical contexts elicit competition for popularity, with high aggression and low prosocial behavior being seen as valuable tools to achieve popularity.